2011
DOI: 10.1002/hc.20747
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity in the coordination of 1,4‐dihydro‐1,4‐diarsinine as a cyclic ditopic organoarsenic ligand to metal ions

Abstract: A number of different complexation structures of cis‐1,4‐dihydro‐1,4‐dimethyl‐2,3,5,6‐tetrakis(t‐butoxycarbonyl)‐1,4‐diarsinine (cis‐DHDAtBu) with gold(I) and iridium(III) were synthesized and characterized by 1H, 13C NMR spectra, X‐ray crystallography, and elemental analysis. Mono‐ and di‐nuclear gold(I) chloride complexes with cis‐DHDAtBu were obtained by simple addition of gold(I) chloride to cis‐DHDAtBu. A hetero‐trinuclear gold‐platinum‐gold complex (PtAu2Cl4(cis‐DHDAtBu)2) was obtained by complexation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…4, gold strings with neutral chain links consist of neutral complexes, which form polymeric gold strings through unsupported aurophilic interactions. [157][158][159][160][161][162][163][164][165][166][167][168][169][170][171] As an example, Ecken et al studied the effect of anions on the solid state structure of (o-xylyl isocyanide)gold(I) (Cl (10a), Br (10b), I (10c), CN (10d)). 172 Their study revealed that the Au-Au distances decrease in the order I − > Br − > Cl − .…”
Section: Neutral Chain Linksmentioning
confidence: 99%
“…4, gold strings with neutral chain links consist of neutral complexes, which form polymeric gold strings through unsupported aurophilic interactions. [157][158][159][160][161][162][163][164][165][166][167][168][169][170][171] As an example, Ecken et al studied the effect of anions on the solid state structure of (o-xylyl isocyanide)gold(I) (Cl (10a), Br (10b), I (10c), CN (10d)). 172 Their study revealed that the Au-Au distances decrease in the order I − > Br − > Cl − .…”
Section: Neutral Chain Linksmentioning
confidence: 99%
“…Dimerization of the E ‐form vinyl radical species produces cyclic diarsenic compounds, cis ‐DHDAs ( 32 ). Platinum, palladium, gold, and copper complexes with cis ‐DHDA ligands ( 33 – 37 ) were synthesized (Scheme ) . Notably, the two arsenic atoms are fixed at a short distance (ca.…”
Section: Conjugated Polymersmentioning
confidence: 99%
“…Platinum,p alladium,g old, and copperc omplexes with cis-DHDA ligands (33)(34)(35)(36)(37)w ere synthesized (Scheme 18). [85][86][87][88][89][90][91][92] Notably,t he two arsenic atoms are fixed at as hort distance (ca. 3 ).…”
Section: Poly(vinylenearsine)smentioning
confidence: 99%